Evolution and biological characteristics of H11 avian influenza viruses isolated from migratory birds and pigeons - Jinyan Shen; Hong Zhang; Xiaohong Sun; Yaping Zhang; Mengjing Wang; Mengdi Guan; Lili Liu; Wenxi Li; Hongke Xu; Yujiao Xie; Anran Ren; Fengyang Cao; et al. (Emerging Microbes and Infections)
The emergence of novel avian influenza reassortants in wild birds in recent years is a public health concern. However, the viruses that circulate in migratory birds are not fully understood. In this study, we summarized and categorized global H11 avian influenza viruses and reported that waterfowl and shorebirds are the major reservoirs of the identified H11 viruses. The surveillance data of the 35,749 faecal samples collected from wild bird habitats in eastern China over the past seven years revealed a low prevalence of H11 viruses in birds, with a positive rate of 0.067% (24 isolates). The phylogenetic analysis of the twenty viruses indicated that H11 viruses have undergone complex reassortment with viruses circulating in waterfowl and shorebirds. These tested viruses do not acquire mammalian adaptive mutations in their genomes and preferentially bind to avian-type receptors. Experimental infection studies demonstrated that the two tested H11N9 viruses of wild bird origin replicated and transmitted more efficiently in ducks than in chickens, whereas the pigeon H11N2 virus isolated from a live poultry market was more adapted to replicate in chickens than in ducks. In addition, some H11 isolates replicated efficiently in mice and caused body weight loss but were not lethal. Our study revealed the role of waterfowl and shorebirds in the ecology and evolution of H11 viruses and the potential risk of introducing circulating H11 viruses into ducks or chickens, further emphasizing the importance of avian influenza surveillance at the interface of migratory birds and poultry.